2017
DOI: 10.1038/s41477-017-0064-y
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of carbohydrate transport in tall trees

Abstract: Trees present a critical challenge to long-distance transport because as a tree grows in height and the transport pathway increases in length, the hydraulic resistance of the vascular tissue should increase. This has led many to question whether trees can rely on a passive transport mechanism to move carbohydrates from their leaves to their roots. Although species that actively load sugars into their phloem, such as vines and herbs, can increase the driving force for transport as they elongate, it is possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
109
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(127 citation statements)
references
References 64 publications
15
109
3
Order By: Relevance
“…Münch thought that this was necessary to prevent pressure loss along the pathway (Münch, , p. 56). This assumption is consistent with the frequent use of the Hagen–Poiseuille equation in models of phloem transport (e.g., Epron, Dannoura, Ishida, & Kosugi, ; Savage et al, ; Thompson & Holbrook, ). Use of Poiseuille‐driven flow has been justified as long as extra equations are included to account for radial water exchange (Thompson & Holbrook, ).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Münch thought that this was necessary to prevent pressure loss along the pathway (Münch, , p. 56). This assumption is consistent with the frequent use of the Hagen–Poiseuille equation in models of phloem transport (e.g., Epron, Dannoura, Ishida, & Kosugi, ; Savage et al, ; Thompson & Holbrook, ). Use of Poiseuille‐driven flow has been justified as long as extra equations are included to account for radial water exchange (Thompson & Holbrook, ).…”
Section: Discussionsupporting
confidence: 81%
“…We found that the most important sieve plate traits that impact plate resistance were total pore area and shape. Previous methodologies take into account the variability of pore radii in their models (Liesche et al, ; Savage et al, ) but assume pores are always circular. However, our results indicate that assuming pore shape as being circular instead of using their actual shape may underestimate pore flow by as much as twofold in comparison with past work (e.g., Jensen, Mullendore, et al, ; Thompson & Holbrook, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations